Crescimento e fisiologia de mudas de Myrocarpus frondosus Allem. (Fabaceae) e Luehea divaricata Mart. & Zucc. (Malvaceae) sob diferentes níveis de sombreamento - Santos, Aldeize da Silva (2016)
Forest species Luehea divaricata Mart. & Zucc. (Malvaceae) commonly called flog horse and Myrocarpus frondosus Allem. (Fabaceae ) as Cabreuva, are well known in Rio Grande do Sul, Brazil, the economic and ecological importance. The goal was to determine the growth and eco-physiological behavior of seedlings subjected to different levels of shading and establish ideal lighting conditions for initial growth. The work was conducted in shade house with four treatments : 0 % (full sun) and 30 %, 50 % and 70% shading. Each treatment had fifteen plants per species. Five plants of each treatment and species were collected in the times of : six, eleven and seventeen months. The measuraments were monthly from June 2014 to October 2015. To cause the shadowing effect was used sombrites. The evaluated and quantified characteristics were: plant height - h; stem diameter - d ; Leaf area - AF ; Specific leaf area - AFE ; Fresh matter content and dry leaves - MFF and MSF ; Fresh root mass - MFR and root dry mass - MSR ; Root volume - VolR ; Fresh stem mass - MFC and dry mass of the stem - MSC ; Number of sheets NF ; Number of shoots (flog Horse) - NB ; Levels of chlorophyll - Tcl , chlorophyll a , chlorophyll , chlorophyll b and total ; Carotenoid content - Carot .; parameres and gas exchange. The collection of data growth and biomass were extended for seventeen months and burrows of gaseous twelve months. Data were analyzed in a completely randomized design. When detected the difference between treatments and between the blocks, applied the Tukey test (α = 0.05). Each month was considered as being a block. In NC and NB, to flog horse and Cabreúva, the highest average occurred during seasons with the greatest amount of light and treatments more lunminosidade and the lowest average in the stations with less light and darker treatments. The AF and AFE to flog the horse 70% with the highest average differed from treatments with more light with less media.O same happened to Cabreuva where the AF in the treatment of 70%, had the highest average differing treatment 0 % who presented lower average. In AFE there were no differences between treatments. The higher levels of photosynthetic pigments occurred in shadow environments plants. The shadow levels combined with ambient lighting enhances the growth of plants the stations with the highest periode of light. Plant growth was sensitive to climatic variations of each season. The plant M. frondosus and L. divaricata adjusted their structures to environments that were entered and according to seasonality to ensure their survival. It can be stated that the species are planted in poultry enrichment merging them with other species that provides shading and microclimate which triggers them to adapt and therefore their healthy growth in the field.